Meninjau Kembali Definisi Riba Era Modern, Pinjaman Uang Kartal (FIAT) Perspektif Studi Islam Fiqih Kontemporer - Saiddaeni, Saiddaeni (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2023)
This article aims to understand the differences in the definition of usury between the time of the Prophet Muhammad and today because it influences the views and laws regarding usury in society. It is important for the parties involved to understand the risks and consequences associated with currency fluctuations before entering into such transactions. As Muslims, understanding how usury is applied in today's context is important in carrying out financial practices that are in accordance with Islamic religious principles. This article uses a literature study method by analyzing a comparative study of the understanding of usury at the time of the Prophet Muhammad with usury in modern times that uses currency (fiat), referring to the book of fiqh in looking at the definition of usury which currently needs to be reviewed. The main purpose of religion forbidding usury is to maintain justice and avoid charging unfair interest, while taking into account risks and other relevant factors in financial transactions. In practice, an understanding of Islamic financial instruments helps choose financial products with sharia principles. So that you can choose a loan that does not involve usury (interest) orgharar (uncertainty) in transactions.